Effect of Antibiotic Treatment Delay on Therapeutic Outcome of Experimental Acute Otitis Media Caused by Streptococcus pneumoniae Strains with Different Susceptibilities to Amoxicillin - Parra, Araceli (American Society for Microbiology, 2004)
The effect of delayed administration of amoxicillin on the course of acute otitis media (AOM) caused by two Streptococcus pneumoniae strains with different susceptibilities to amoxicillin (MICs of 0.016 and 1 μg/ml for strains A and B, respectively) was evaluated in the gerbil model. The organisms were inoculated by transbullar challenge into the middle ear, and antibiotic treatment was administered at various times thereafter. The bacteriological and clinical efficacies of treatment diminished significantly with the delay of antibiotic administration. The bacterial eradication rates when antibiotic treatment was started at 2, 5, 8, 18, and 21 h post-bacterial inoculation were different for both strains (95, 95, 90, 55, and 55% for strain A and 95, 95, 65, 10, and 0% for strain B). Results of further experiments using strain B with higher antibiotic doses and numbers of administrations and different follow-up times indicate that the failures observed with the delayed administration were not related to the bacterial burden, selection of antibiotic-resistant mutants, or inadequate pharmacodynamic parameters. Such failures may be related to the metabolic bacterial status. The delayed amoxicillin treatment of AOM caused by S. pneumoniae may lead to therapeutic failures, mainly when organisms with diminished antibiotic susceptibility are involved.